ANALISIS JARINGAN SOSIAL PASAR SUNDAY MORNING (SUNMOR) DI UNIVERSITAS GADJAH MADA YOGYAKARTA - Nur Islami, Mona Erythrea (Sekolah Tinggi Pariwisata AMPTA, 2016)
Sunday Morning market is a weekly market that is open on Sundays morning at Gadjah Mada University area. It is a place for informal traders to sell their goods. The analysis shows that there are some patterns of social networks between traders, suppliers and buyers in Sunday Morning market. The formation of social networks among traders is a horizontal network, based on kinship ar friendship. They have the same resources and obligations to be exchanged. The social relationship itself will be manifested in help each others. The social networks formed through kinship has important role to overcome social pressures, poverty, unemployment and limited access in getting economic resources. It is common in the informal trading sector, traditional management applied based on friendship, kinship or origin. The formation of social networks between traders and suppliers is such a vertical social networks, by which the socio-economic status is not worth, as well the exchanged of obligations and resources.The relation between them is patron-client relationship. Whereas, social networks between sellers and buyers is based on the network of interest, social networks between sellers and buyers based on the network of interest in each other. Keywords : patterns of social networks, traders, suppliers, buyers, Sunday Morning market